In-Silico Prediction of the Physical Performance of Pharmaceutical Crystals - Hamad, Mustafa (Curtin University, 2021)
Knowledge of the hardness of pharmaceutical crystals expedites the large-scale manufacturing of drug tablets. This research involved the development and testing of computational methods to simulate the various deformations of crystals that lead to the calculation of hardness. Both methods were applied to a range of materials and provided a consistent ranking of the slip systems with experiment, a detailed atomistic description of the deformation mechanisms, and the calculation of ideal shear strength.